PENGETAHUAN WIRAUSAHA, MOTIVASI BERWIRAUSAHA, KONDISI SOSIAL EKONOMI DAN LINGKUNGAN KELUARGA, PENGARUHNYA TERHADAP MINAT BERWIRAUSAHA IBU RUMAH TANGGA - Nurdiana Nurdiana; Rahmatullah Rahmatullah; Muhammad Hasan; Nurjannah Nurjannah; Fitriani Fitriani (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
This study aims to determine and see the effect of Entrepreneurship Education, Entrepreneurial Motivation, Socio-Economic Conditions and Family Environment on Housewife Entrepreneurial Interests in Wele Village, Wajo Regency. The method used is quantitative, and the method of collecting information is through observation, questionnaires or questionnaires and documentation. The number of samples in this review were 81 housewives in Wele Village which were then analyzed using various examinations, namely multiple linear regression analysis. Judging from the final results of the review, it tends to be seen that the four variables (X) jointly affect the interest in doing business among housewives in Wele Village (Y). However, based on a partially significant test, the entrepreneurial knowledge variable (X1) and the socio-economic condition variable (X3) had a positive but not significant effect, while the variable from entrepreneurial motivation (X2) and also the family environment (X4) influenced housewives’ entrepreneurial interest ( Y) positively and significantly. Keywords:  entrepreneurial knowledge level, entrepreneurial motivation, socio economic conditions; family environment; entrepreneurial interest